2011
DOI: 10.1007/s12013-011-9173-9
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Assessment of the Effect of Ginkgo biloba Leave Extract (EGb 761) on Mammalian Retina

Abstract: Ginkgo biloba extract has been therapeutically used for several decades to increase peripheral and cerebral blood flow as well as for the treatment of dementia. The extract contains multiple compounds such as flavonoids and terpenoids that are thought to contribute to its neuroprotective and vasotropic effects. In this study, we investigated the effect of prolonged administration of EGb 761, up to 10 weeks, on mammalian retina using Fourier transform infrared spectroscopy (FTIR). Two main groups were involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Changes in OH modes indicate the formation of hydrogen bonds with different structural states [12]. Moreover the exposure to H 2 S gas has no effect on the CH stretching region that arising from lipid [13].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Changes in OH modes indicate the formation of hydrogen bonds with different structural states [12]. Moreover the exposure to H 2 S gas has no effect on the CH stretching region that arising from lipid [13].…”
Section: Discussionmentioning
confidence: 98%
“…Intermolecular β-sheet interactions (band < 1620 cm -1 ) are associated with bimolecular recognition, protein quaternary structure, proteinprotein interactions and peptide and protein aggregation. While, intramolecular β-sheet interactons (band between 1630-1620 cm -1 ) are associated with protein folding [13]. Thus, vibrational spectra, as those of the FTIR spectra, were directly related to the structural features of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This qualifies as a PAT claim as it qualitatively sets up the variability source, clarifies its dissemination to the final product quality traits, and also can be practiced as a control policy in the production steps . Though FTIR has not been used exhaustively as an active PAT tool for G. biloba extracts, the results of a very recent work show promise . The effects of G. biloba Leave extract (EGb 761) were studied on the mammalian retina through FTIR analysis.…”
Section: Integration Of Pat With Traditional Drug Manufacturingmentioning
confidence: 99%
“…The effects of G. biloba Leave extract (EGb 761) were studied on the mammalian retina through FTIR analysis. According to the authors, their work demonstrated different positive effects on the retinal components (amide I protein secondary structure constituents and the NH–OH region) . This indicates that FTIR can be an effective PAT strategy, though other advanced and relevant studies need to justify this.…”
Section: Integration Of Pat With Traditional Drug Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation